1994
DOI: 10.1113/expphysiol.1994.sp003785
|View full text |Cite
|
Sign up to set email alerts
|

The role of parathyroid hormone‐related protein in calcium homeostasis in the fetal pig

Abstract: The concentrations of plasma parathyroid hormone‐like bioactivity and parathyroid hormone‐related protein (1–86) (PTHrP) immunoreactivity were both higher in fetal pigs than in their mothers during the last 3 weeks of gestation. Both activities changed inversely with alterations in the plasma ionized calcium concentration. The data suggest that PTHrP may have a role in calcium homeostasis in the fetal pig, similar to its postulated role in sheep in the stimulation of calcium transport across the placenta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Cytochemical assays have revealed that fetal blood contains high PTH-like bioactivity, which cannot be accounted for by the low immunoreactive levels of PTH (3,20,67). Following the discovery of PTHrP and the development of specific radioimmunoassays for it, studies in fetal pigs (7) and sheep (94,396) determined that high immunoreactive levels of PTHrP correlated closely with, and likely accounted for, the high PTH-like bioactivity in fetal blood.…”
Section: Pthrpmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytochemical assays have revealed that fetal blood contains high PTH-like bioactivity, which cannot be accounted for by the low immunoreactive levels of PTH (3,20,67). Following the discovery of PTHrP and the development of specific radioimmunoassays for it, studies in fetal pigs (7) and sheep (94,396) determined that high immunoreactive levels of PTHrP correlated closely with, and likely accounted for, the high PTH-like bioactivity in fetal blood.…”
Section: Pthrpmentioning
confidence: 99%
“…Venous umbilical PTHrP levels are higher than umbilical arterial levels in pigs, which suggests that the placenta may be an important source of circulating PTHrP in the fetus (7). As discussed in section IIC, the fetal parathyroids were originally proposed to be the source of PTHrP in fetal sheep, but the effect of fetal parathyroidectomy on the plasma PTHrP concentration was not reported.…”
Section: Pthrpmentioning
confidence: 99%
See 1 more Smart Citation
“…In most tissues in which PTHrp is expressed, target cells for PTHrp were found adjacent. They often respond to PTHrp by an activation of adenylate cyclase (AC) and subsequently protein kinases A (PKA) (2,3), but this is not a general rule. In fact, keratinocytes have been shown to respond to the PTHrp they produce and secrete, by a yet uncharacterized receptor, which uses calcium ions as a second messenger and thus is associated to the protein kinase C (PKC) pathway (4).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that a recombined PTHrP induces hypercalcaemia and bone resorption, stimulates phosphate transport and augments cAMP synthesis in kidneys and in bone cells [32]. The fragment 67-86 stimulates transport of calcium ions across the placenta from the mother to her foetus [1]. The fragment 67-86 stimulates transport of calcium ions across the placenta from the mother to her foetus [1].…”
Section: Introductionmentioning
confidence: 99%